Cancer occurrence in patients with inflammatory bowel disease in treatment with anti-TNF: report of three cases and literature review - Amaral, Lucas Camargo Gamba Martins do; Correa, Luiz Henrique Locks; Accord, Cassiano Coral; Santos, Thamy dos; Kock, Beatriz de Oliveira; Kock, Kaiser de Souza (Brazilian Journal of Oncology, 2021)
Case report of three patients with inflammatory bowel disease who underwent treatment with biology therapy and developed respectively: non-Hodgkins lymphoma, colorectal adenocarcinoma, and cholangiocarcinoma after long-term follow-up. They demonstrated that data are currently inconclusive about the development of long-term anti-TNF neoplasias.
Keywords: Inflammatory bowel diseases; Tumor necrosis factors; Lymphoma; NonHodgkin; Cholangiocarcinoma.